-3(3u-1)+5u=9+4(2u-4)

Simple and best practice solution for -3(3u-1)+5u=9+4(2u-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3u-1)+5u=9+4(2u-4) equation:


Simplifying
-3(3u + -1) + 5u = 9 + 4(2u + -4)

Reorder the terms:
-3(-1 + 3u) + 5u = 9 + 4(2u + -4)
(-1 * -3 + 3u * -3) + 5u = 9 + 4(2u + -4)
(3 + -9u) + 5u = 9 + 4(2u + -4)

Combine like terms: -9u + 5u = -4u
3 + -4u = 9 + 4(2u + -4)

Reorder the terms:
3 + -4u = 9 + 4(-4 + 2u)
3 + -4u = 9 + (-4 * 4 + 2u * 4)
3 + -4u = 9 + (-16 + 8u)

Combine like terms: 9 + -16 = -7
3 + -4u = -7 + 8u

Solving
3 + -4u = -7 + 8u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-8u' to each side of the equation.
3 + -4u + -8u = -7 + 8u + -8u

Combine like terms: -4u + -8u = -12u
3 + -12u = -7 + 8u + -8u

Combine like terms: 8u + -8u = 0
3 + -12u = -7 + 0
3 + -12u = -7

Add '-3' to each side of the equation.
3 + -3 + -12u = -7 + -3

Combine like terms: 3 + -3 = 0
0 + -12u = -7 + -3
-12u = -7 + -3

Combine like terms: -7 + -3 = -10
-12u = -10

Divide each side by '-12'.
u = 0.8333333333

Simplifying
u = 0.8333333333

See similar equations:

| (7r^3-6r-6)(2r-4)= | | 62(x+20)=90 | | -(y+15)+2y-12=-42 | | t^3-10t+21=0 | | 9(s+6)-8s=45 | | 12x+11=13x+9 | | 4(8)+3y=35 | | 16t^2-96t-12=152 | | -1.8-3=7w-5.5-6w | | 12-40= | | 16-(2m+8)=4+3m-11 | | 4(w-5)-6=-4(-4w+9)-6w | | -10-6p+7p=-9 | | -21x-63=-126 | | 3x/4x-5/6=2x/3x | | 8s-4-7s=2-1 | | -0.53k=3.498 | | 16t^2-96t-4=144 | | 3x^2+18x=8 | | 3x(2x+10)=-24 | | m^2+(m-6)m= | | 12x+2=13x+9 | | 4r+3=r+27 | | 4x-1=4+4x+3 | | 23-3x=50 | | 2(w+2)=-6(2w-3)+6w | | 1x/4x+1/2=1x/4x-1/2 | | 0=70 | | 5x-52+2x=2-9x+10 | | 2(a-4)=4a-2(a+4) | | 5+5x-7x=3 | | 6x-25=25-9x |

Equations solver categories